2022
DOI: 10.1002/jev2.12213
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins distinguish separate extracellular vesicle subpopulations in human serum and plasma – Contributions of platelet extracellular vesicles in plasma samples

Abstract: Background: The ability to isolate extracellular vesicles (EVs) from blood is vital in the development of EVs as disease biomarkers. Both serum and plasma can be used, but few studies have compared these sources in terms of the type of EVs that are obtained. The aim of this study was to determine the presence of different subpopulations of EVs in plasma and serum. Method: Blood was collected from healthy subjects, and plasma and serum were isolated in parallel. ACD or EDTA tubes were used for the collection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 60 publications
10
99
4
Order By: Relevance
“…However, few studies have found that some cells secreting EVs may carry the surface markers of those cells [ 13 ]. New studies also confirm that, for example, CD41a-positive EVs in plasma are most likely secreted by platelets [ 14 ], providing some theoretical basis for our discussion (see below). However, the pathways by which EVs are activated and released are not the same.…”
Section: Secretion and Activation Of Extracellular Vesicles From Vari...supporting
confidence: 64%
“…However, few studies have found that some cells secreting EVs may carry the surface markers of those cells [ 13 ]. New studies also confirm that, for example, CD41a-positive EVs in plasma are most likely secreted by platelets [ 14 ], providing some theoretical basis for our discussion (see below). However, the pathways by which EVs are activated and released are not the same.…”
Section: Secretion and Activation Of Extracellular Vesicles From Vari...supporting
confidence: 64%
“…In fact, other researchers demonstrated the prevalence of CD9+ EVs in blood with differences in concentration according to anti-coagulants, plasma, or serum biofluid type, and isolation method, while CD81+ EVs were the rarest tetraspanin in both plasma and serum, and CD63+ EVs were enriched in serum. However, the researchers affirmed that CD63 is present in multiple subpopulations of EVs, and both CD63+ and CD81+ EVs were less affected by the type of anticoagulant used [ 40 ]. In addition, it has been demonstrated that the tetraspanin composition of EVs differs according to the collected SEC fractions [ 25 ], as well as to their cellular origin, which might influence the selection of target cells and the mechanism of EV uptake [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it remains unclear whether distinct EV subsets exist in plasma and serum. According to the research, blood sampling methods, including the anticoagulant used and the centrifugation protocol chosen, might influence the EV analysis [77]. By combining size-exclusion chromatography (SEC) with OptiPrep density gradient centrifugation, Vergauwen et al [78] fractionated blood plasma to obtain EVs for a deeper biological understanding of EVs and the development of biomarkers.…”
Section: Diagnostic Technologymentioning
confidence: 99%